Hemogram of elderly in a clinical analysis in the city of Ivai-PR (Research, Society and Development, 2021)
Over time, the human body undergoes a natural aging process, generating functionaland structural changes. At this stage of life, follow-up is necessary. Laboratory tests such as blood counts are an ideal tool to assess blood and its components, containing data from erythrogram, white blood cell count, and platelet count. The objective of this research was to know the prevalence of quantitative alterations in the blood count of the elderly in a clinical analysis laboratory in Ivaí-PR, from January 2019 to January 2021. The criteria for data analysis were patients aged 60 years or more and complete registration in the laboratory's internal system. After analyzing the data, it was possible to classify the anemias found, as well as to assess the cellular portion of elderly individuals. Of the 597 hemograms evaluated, it was observed that the majority of the elderly (53.93%) were female and 46.07 were male, (26.70%) were aged between 60-65 years. In the hematological profile of the elderly analyzed, anemia was found in 19.57% of women and 16.73% of men. In the hematimetic indices (VCM, HCM, CHCM and RDW) most were within the reference values, being respectively: 90.47%, 84.09%, 98.99% and 68.17%. Leukocytosis was verified in 2.85% of the sample and thrombocytosis in1.34%. Among all hemograms, there was a leukemia with morphological characteristics of chronic lymphoid leukemia (1.67%). Despite the age and frailty of the patients, it is concluded that the majority has a blood count within the range considered normal.